Clinical benefits and risks of remote patient monitoring: an overview and assessment of methodological rigour of systematic reviews for selected patient groups - Constanze Wartenberg; Helen Elden; Malte Frerichs; Lennart L Jivegård; Kajsa Magnusson; Georgios Mourtzinis; Ola Nyström; Kajsa Quitz; Helen Sjöland; Therese Svanberg; Helena Vallo Hult (BMC Health Services Research)
Abstract Background Remote patient monitoring implies continuous follow-up of health-related parameters of patients outside healthcare facilities. Patients share health-related data with their healthcare unit and obtain feedback (which may be automatically generated if data are within a predefined range). The goals of remote patient monitoring are improvements for patients and reduced healthcare costs. The aim of this paper is to provide an overview of systematic reviews regarding remote patient monitoring for selected patient groups currently considered for the introduction of remote patient monitoring in Region Västra Götaland, Sweden. The selected sixteen patient groups were: patients with asthma, chronic obstructive pulmonary disease, children and adolescents with complex needs, children and adolescents with cystic fibrosis, children and adolescents with periodic fever, elderly patients with multiple diseases, patients with eye diseases, heart failure, haematological disease, hypertension, inflammatory bowel disease, neurorehabilitation, Parkinson’s disease, psoriasis, sleep apnea, and specialist maternity care. Outcomes considered in this overview were patient-relevant clinical benefits as well as risks. Methods A literature search for systematic reviews of clinical trials on remote patient monitoring in the selected patient groups was conducted by two information specialists, followed by assessment of relevance by a team of clinical and methodological experts in Region Västra Götaland, Sweden. The methodological rigour of identified systematic reviews was assessed using QUICKSTAR – a tool for stepwise appraisal of systematic reviews. In a QUICKSTAR assessment, a level of at least five is considered a prerequisite for reliable conclusions regarding the question at issue. Results The literature search resulted in 4,049 hits, of which 84 SRs were considered relevant for the question at issue. A QUICKSTAR level of at least five was reached by 13 (15%) of the relevant systematic reviews. Some patient benefit of remote patient monitoring was reported for five patient groups (asthma, chronic obstructive lung disease, heart failure, hypertension, and elderly patients with multiple diseases). For four patient groups (children with complex needs, children with cystic fibrosis, specialist maternity care, and sleep apnea), systematic reviews of adequate quality concluded that scientific evidence on clinical patient benefits of remote monitoring is very limited. For seven patient groups, no systematic reviews of sufficient quality were identified. Conclusion Clinical benefits and risks of remote patient monitoring as a replacement for, or in addition to, standard of care compared to standard of care (face-to-face visits) are poorly studied for most of the selected patient groups based on systematic reviews of acceptable quality. Patient-relevant clinical benefits are limited or impossible to evaluate for most diagnoses based on currently available scientific information. Possible clinical risks and costs are poorly studied.